KOBUS PORRECTICORNIS (REDUNCINI) FROM THE UPPER SIWALIKS OF TATROT, - PAKISTAN A. Iqbal; A.M Khan; M. Akhtar (Journal of Animal and Plant Sciences, 2015)
This paper presents newly discovered Reduncine fossils which are collected from the Tatrot Zone, of Soan Formation in the Upper Siwaliks of Pakistan. Reduncines are basically obligate grazers and have their dwellings in swamps, grassland, and Savanna woodland and even dry land having a source of water. The specimens under study include the lower teeth and exhibit the diagnostic characters of Kobus (Reduncini) including a distinct goat fold, a less sharp basal pillar, and a transverse flange at posterior side and a less constricted lobes at labial side. Reduncini recognized on the basis of rounded shape cusps while other bovids have blunt cusps is a prominent feature of this tribe. The present specimens are identified as Kobus porrecticornis on the basis of similarities with the already known specimens from the Upper Siwaliks. stratigraphic importance of the Upper Siwaliks has been
Keywords: Bovidae; Pleistocene; Siwaliks; Antelope; Reduncini; Molar.